Implementasi Csr (Corporate Social Responsibility) Di Koperasi Simpan Pinjam Maju Wijaya Dalam Meningkatkan Perkembangan Usaha Mikro Kecil Dan Menengah (Umkm) - Sidhi Agustiana Taniman (Universitas Tarumanagara, 2019)
UMKM (Mikro Kecil dan Menenagah) is the hope of the Republic of Indonesia to continue to grow and develop, but this is not in line with the development of UMKM, so many obstacles encountered, therefore the responsibility to empower UMKM is not only a responsibility. from the government, the responsibility of the company to participate in empowering UMKM through corporate social responsibility activities to the community in general and UMKM, especially in the form of CSR. Corperate Social Responsibility (CSR) is the way companies do to contribute or participate in providing benefits to the wrong perpetrators of society. The activities of Corperate Social Responsibility (CSR) have been undertaken by companies based on the cooperative, Koperasi Simpan Pinjam Maju WIjaya in increasing the development of UMKM through Corperate Social Responsibility (CSR) activities. The method used is descriptive qualitative method which is usually done for case study and data completion which is used using the interview technique, and take from written sources from books, journals and documentation related to Kopeasi Simpan Pinjam Maju Wijaya in data management so that the result of it can be useful information. To conduct the activities of Corporate Social Responsibility (CSR) to UMKM conducted by Koperasi Simpan Pinjam Maju Wijaya through five key successes namely Education, Discussion Group Forum, Assistance, Periodical Visits, Periodic Information for True CSR Activity can benefit UMKM.